The Methodology of Delayed Interaction Techniques Application in L2 Asynchronous Learning and Teaching - Kolisnichenko, Anhelina (Educational Challenges, 2023)
In the new global education, online learning and teaching have become central issues for different methodology development. This paper examines the ways for asynchronous foreign language teaching mode. The purpose of this study is to define specific techniques that are applicable to asynchronous interaction in the process of foreign language learning and teaching. The aim of this paper is also to work out the methodology for their use. Methodology. For this study, a number of research methods were used. The previous studies' analysis was used for the examination of the recent findings. A qualitative case-study experiment was used to investigate personal teachers and students’ experience with delayed interaction techniques (DIT) use in the process of Foreign Language (FL) Methodology teaching and learning that is a component of FL teachers training course in the department of foreign languages of Pavlo Tychyna Uman State Pedagogical University in Ukraine. The methodological approach offered an effective way of compiling delayed interaction technique stages. Data were gathered from the students’ feedback survey that was used as a qualitative method. The online software of the Voyant tool, one of the more practical ways for survey results visualization was applied. Results. One of the main findings of the current study is a clarification of the delayed interaction technique notion, which is suggested as a definition in the context of the current study issue. The second finding is developing the methodology of using DIT in a second language (L2) asynchronous learning and teaching mode of studying. The methodology includes seven steps for DIT application. Conclusions. This study has found that generally, interaction is possible to use even asynchronically in conditions that prevent immediate interaction. The results of this study have no limitations for application according to educational institutions, and learners’ age of L2 level. However, for effective DIT applications, it is necessary for teachers and students to have enough digital skills, internet and gadgets access. Further work needs to be done to examine more online resources such as software, apps, and tools for using them in asynchronous L2 learning and teaching.